Foresight Competency Styles Upon Academic Leaders at King Abdulaziz University - Al-Maghdi, Muidh Saleh (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the reality of foresight competence styles upon academic leaders at king Abdulaziz University. and to reveal if there are statistically significant differences between academic leaders due to the different variables (gender, years of experience). The researcher used the descriptive approach, in its survey style, and the researcher used the Foresight Styles Assessment (FSA) scale designed by (Dian, 2009) and developed by (Gary, 2009) and distributed to a sample of (50) individuals from the study population, whose number is (350), and the study concluded that the efficiency of foresight among academic leaders at King Abdulaziz University in general came with an average of (3.84 out of 5), that is, with a (high) efficiency. As for their prevailing foresight patterns, the (adaptive) pattern came in the first order; With an average of (4.01), then the insightful with an average of (3.93) and thirdly the experimenter with an average of (3.80), all of them with a degree of efficiency (high) and finally the pattern of waiting with an average of (3.36) and an estimate of efficiency (medium), and the results concluded that there are no statistically significant differences at the level of significance (0.05). ) between the averages of the academic leaders’ responses about the patterns of their foresight efficiency, in their four types, according to the variables of gender or years of experience. In light of the previous results, the researcher recommended the establishment of a center at King Abdulaziz University to be concerned with forward-looking studies; To develop the capabilities of the foresight leaders, and invest them in carrying out prospective studies in all fields, and to disseminate and enhance the skills and tools of scientific foresight in the academic community at King Abdulaziz University and all universities in the Kingdom.